Shiga toxin in enterohemorrhagic E.coli: regulation and novel anti-virulence strategies - Sperandio, Vanessa; Pacheco, Alline R. (Frontiers in Cellular and Infection Microbiology, 2012)
Enterohemorrhagic Escherichia coli (EHEC) are responsible for major outbreaks of bloody diarrhea and hemolytic uremic syndrome (HUS) throughout the world. The mortality associated with EHEC infections stems from the production and release of a potent Shiga toxin (Stx) by these bacteria. Stx induces cell death in endothelial cells, primarily in the urinary tract, causing HUS. Stx was first described in Shigella dysenteriae serotype I by Kiyoshi Shiga and was discovered later in EHEC. Multiple environmental cues regulate the expression of Stx, including temperature, growth phase, antibiotics, reactive oxygen species (ROS), and quorum sensing. Currently, there is no effective treatment or prophylaxis for HUS. Because antibiotics trigger Stx production and their use to treat EHEC infections is controversial, alternative therapeutic strategies have become the focus of intense research. One such strategy explores quorum sensing inhibitors as therapeutics. These inhibitors target quorum sensing regulation of Stx expression without interfering with bacterial growth, leading to the hypothesis that these inhibitors impose less selective pressure for bacteria to develop drug resistance. In this review, we discuss factors that regulate Stx production in EHEC, as well as novel strategies to prevent and/or minimize the development of HUS in infected subjects.